Characterization of the changes of aroma profiles in large-leaf yellow tea during processing using GC–MS and electronic nose analysis - Xiangyang Guo; Wilfried Schwab; Chi-Tang Ho; Chuankui Song; Xiaochun Wan (Food Chemistry: X)
Tea processing is vital for aroma formation of large-leaf yellow tea (LYT), yet the volatile compounds during its processing remain poorly understood. Volatile profiles of LYT throughout the processing were characterized by gas chromatography–mass spectrometry and electronic nose (E-nose). Distinct differences in volatile compositions were observed among stages, with 178 volatiles identified, dominated by alcohols during processes. Notably, heterocyclic compounds became prominent after full fire processing, during which 30 N-containing compounds were newly generated, making a significant shift in the volatile profile. Furthermore, tea samples can be distinguished based on the identified volatiles or the responses of E-nose, implying that E-nose is suitable for the detection of volatiles in tea production. Additionally, the aroma-active compounds of LYT were widely different from those of other types of yellow teas, attributed to the unique critical processes involved. These results provide valuable theoretical guidance for the processing and quality control of LYT.